IIUM: The premier global Islamic university - Kamaruddin, Zaleha (IIUM Press, 2013)
The International Islamic University Malaysia (IIUM) in thirty years, since its inception in 1983, has emerged as a leading institution of higher learning producing graduates, delivering education, new knowledge and innovation for the needs of the Ummah and world at large. It has internationally competitive faculty and an energetic and enthusiastic student body enriching themselves in an Islamic enviroment which is technologically rich and laced with a universe of culture and ideas. The thirty years history of the University has been thirty years of educational development from Islamic and international perspectives. This has been very well documented in this book which is co-edited by the first lady Rector of IIUM. Zaleha Kamaruddin